(untitled) (International Journal of Engineering and Computer Science, 2017)
.This paper addresses the problem of recovering 3D non-rigid shape models from image sequences. For example, given a video recording of a talking person, we would like to estimate a 3D model of the lips and the full head and its internal modes of variation. Many solutions that recover 3D shape from 2D image sequences have been proposed; these so-called structure-from-motion techniques usually assume that the 3D object is rigid. Previous work has treated the two problems of recovering 3D shapes from 2D image sequences and of discovering a parameterization of non-rigid shape deformations separately. Most techniques that address the structure-from-motion problem are limited to rigid objects